2023
DOI: 10.1021/jacs.2c09501
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Low-Frequency Pulsed Strategy Enables Ultralong CO2 Reduction Stability and Controllable Product Selectivity

Abstract: Copper-based catalysts are widely explored in electrochemical CO2 reduction (CO2RR) because of their ability to convert CO2 into high-value-added multicarbon products. However, the poor stability and low selectivity limit the practical applications of these catalysts. Here, we proposed a simple and efficient asymmetric low-frequency pulsed strategy (ALPS) to significantly enhance the stability and the selectivity of the Cu-dimethylpyrazole complex Cu3(DMPz)3 catalyst in CO2RR. Under traditional potentiostatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
38
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 46 publications
3
38
0
Order By: Relevance
“…Electroreduction of carbon dioxide (CO 2 RR) to value-added products using renewable energy offers a feasible pathway to realize carbon-neutral energy cycle. , Among various CO 2 RR products, multicarbon (C 2+ ) products, such as C 2 H 4 , C 2 H 5 OH, and CH 3 COOH, have attracted wide attention due to their high energy densities. Efficient CO 2 -to-C 2+ convention involves multiple proton-coupled electron transfer processes, which accompanied with multiple intermediates on catalytic sites often lead to a low activity and selectivity. Therefore, it is important and challenging to develop effective electrocatalysts for CO 2 RR. , Copper (Cu) materials showed great promise to promote selective electroreduction of CO 2 to C 2+ products with a high conversion efficiency. Recent studies have demonstrated that the moderate oxidation state of Cu (Cu δ+ ) played a critical role in steering the CO 2 RR pathway toward the high-efficacy C 2+ formation. However, Cu δ+ active sites are extremely unstable during CO 2 RR, and various strategies, including plasma treatment, heteroatom doping, and organic molecular modification, have been explored to stabilize Cu δ+ . ,, Recent advances have improved the Faradaic efficiency (FE) toward C 2+ products up to around 80 to 90%. , In spite of these efforts, Cu δ+ sites still suffer from the in situ self-reduction during CO 2 RR. This makes it very difficult to maintain a high CO 2 RR activity, especially at high operating current densities …”
Section: Introductionmentioning
confidence: 99%
“…Electroreduction of carbon dioxide (CO 2 RR) to value-added products using renewable energy offers a feasible pathway to realize carbon-neutral energy cycle. , Among various CO 2 RR products, multicarbon (C 2+ ) products, such as C 2 H 4 , C 2 H 5 OH, and CH 3 COOH, have attracted wide attention due to their high energy densities. Efficient CO 2 -to-C 2+ convention involves multiple proton-coupled electron transfer processes, which accompanied with multiple intermediates on catalytic sites often lead to a low activity and selectivity. Therefore, it is important and challenging to develop effective electrocatalysts for CO 2 RR. , Copper (Cu) materials showed great promise to promote selective electroreduction of CO 2 to C 2+ products with a high conversion efficiency. Recent studies have demonstrated that the moderate oxidation state of Cu (Cu δ+ ) played a critical role in steering the CO 2 RR pathway toward the high-efficacy C 2+ formation. However, Cu δ+ active sites are extremely unstable during CO 2 RR, and various strategies, including plasma treatment, heteroatom doping, and organic molecular modification, have been explored to stabilize Cu δ+ . ,, Recent advances have improved the Faradaic efficiency (FE) toward C 2+ products up to around 80 to 90%. , In spite of these efforts, Cu δ+ sites still suffer from the in situ self-reduction during CO 2 RR. This makes it very difficult to maintain a high CO 2 RR activity, especially at high operating current densities …”
Section: Introductionmentioning
confidence: 99%
“…1 Among the clean technologies, the electrocatalytic reduction of CO 2 for value-added products using clean electric energy stands out as a particularly attractive and promising solution to reduce carbon emissions. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] To date, many Au-, Ag-, and Cu-based nanostructured materials, metal-organic frameworks, and single-atom catalysts have been developed to apply in the CO 2 electroreduction reaction (CO 2 RR). [16][17][18][19][20][21][22] However, the CO 2 RR generally faces challenges in achieving high selectivity and a high current density due to the intrinsic thermodynamic stability of CO 2 and the competitive hydrogen evolution reaction (HER), hindering its practical application.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some additional applied physical fields have been proven to improve the deposition state of lithium metal [36,37]. Gu et al grew in situ Cu matrix clusters with a tunable oxidation state in Cu 3 (DMPz) 3 by using a simple pulsed method and achieved a high CO2RR performance and ultralong cycling by enhancing their selectivity to C 2 H 4 [38]. Zai et al also prepared Te nanowires with a uniform morphology by controlling the nucleation and growth of crystals via pulsed physical deposition [39].…”
Section: Introductionmentioning
confidence: 99%